ANALYSIS OF THE ERADICATION OF TERRORISM CRIME BY DETACHMENT 88 IN INDONESIA - Paputungan, Jayadi (Jurnal Hukum Volkgeist, 2019)
community anxiety about criminal act of the terrorist. Because of that, The Government makes a Substitution Regulation Act No. 1 of 2002. Afterwards, The Government demands Indonesian Police Chief to make Specific Detachment that called Densus 88, to carry out Regulations Act No. 5 of 2018 on the changes to the Act No. 15 of 2003 about ?The Determination of Substitute Government Regulations Act No. 1 of 2002 Concerning The Eradication of Criminal Act Terrorism.?. Problem Formulations 1) How Densus 88 eradicates the criminal act terrorism? 2) How the actions form of Densus 88 in terms of human rights side? In fact, Densus 88 is not in accordance with the applicable regulation, the field fact shows that many terrorist suspect suffered injuries and even died and it also against the human rights. The research method used normative juridical method; law is seen as a binding rule. The conclusion of this research is the action taken isn?t appropriate with the threats faced, it is not accordance with the law principle and law basis that should be. In addition, it carries out human rights violations which are harmful for the suspect and the terrorist defendant, then the lack of State responsibilities for things that happened.